2022
DOI: 10.3390/biomedicines10071515
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Changes in Thyroid Cancers and the Importance of Their Preoperative Detection in Relation to the General Treatment and Determination of the Extent of Surgical Intervention—A Review

Abstract: Carcinomas of the thyroid gland are some of the most common malignancies of the endocrine system. The causes of tumor transformation are genetic changes in genes encoding cell signaling pathways that lead to an imbalance between cell proliferation and apoptosis. Some mutations have been associated with increased tumor aggressiveness, metastatic lymph node spread, tendency to dedifferentiate, and/or reduced efficiency of radioiodine therapy. The main known genetic causes of thyroid cancer include point mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“… 8 The main known genetic causes of thyroid cancer include point mutations in the BRAF, RAS, TERT, RET , and TP53 genes and the fusion genes RET/PTC, PAX8/PPAR-γ , and NTRK . 9 Fusion gene positive PTCs were associated with more aggressive behavior disease than fusion gene negative PTCs. 10 A comprehensive study reported by Pekova et al recently identified that RET fusion was associated with a 100% probability of malignancy.…”
Section: Introductionmentioning
confidence: 94%
“… 8 The main known genetic causes of thyroid cancer include point mutations in the BRAF, RAS, TERT, RET , and TP53 genes and the fusion genes RET/PTC, PAX8/PPAR-γ , and NTRK . 9 Fusion gene positive PTCs were associated with more aggressive behavior disease than fusion gene negative PTCs. 10 A comprehensive study reported by Pekova et al recently identified that RET fusion was associated with a 100% probability of malignancy.…”
Section: Introductionmentioning
confidence: 94%
“…This mutation activates BRAF kinase, which phosphorylates multiple targets, including MEK and ERK [ 49 ]. The BRAF V600E mutation is observed in approximately 20–40% of ATCs [ 50 ], and Jannin et al [ 12 ]. reported that the frequency of BRAF mutations in ATCs appears to vary in each region.…”
Section: The Characteristics Of Atcmentioning
confidence: 99%
“…Although, FNA differentiates benign from malignant thyroid nodules in an appropriate manner, in approximately 30% of patients persists diagnostic difficulties for nodules categorized with indeterminate cytology, comprising atypia of undetermined significance or follicular lesion of undetermined significance (TBSRTC III, AUS/FLUS) and follicular neoplasm (TBSRTC IV, FN/SFN) or Hürthle cell neoplasm (TBSRTC IV, HCN/SHCN) [42,43]. The AAES recommends for TBSRTC III nodules, in addition to the other guidelines, to reckon with clinical factors, radiologic features, and patient preference about repeat biopsy, molecular testing, diagnostic thyroidectomy, or observation [2,4,6].…”
Section: Paraclinical Assessment and Managementmentioning
confidence: 99%